Unsafe abortions: the plight of the womb - Kaur, Harpreet; Nandrajog, Anchal; Shivanna, Nischitha; Kaur, Sarvjeet (International Journal of Research in Medical Sciences, 2023)
Abortion is a common health care intervention in women of reproductive age group. It is reported that 6 out of 10 unintended pregnancies and 3 out of 10 of all pregnancies end up in induced abortion. Developing countries bear the burden of 97% of unsafe abortion and they account for 5-13% of maternal mortality. We have attempted to present a case series on unsafe abortions dealt with in our facility. It was a prospective observational study conducted over patients admitted in the department of OBG, GGSMCH, Faridkot over a period of 14 months. The patients presenting with post abortal complications constituted the study population. Out of the total 100 patients, 40 patients gave history of unsafe abortion; of whom 18 patients with grade 4 sepsis were included in study. Laparotomy was done in 12 patients, out of which there were 3 uterine repair, 1 intestinal repair and only peritoneal washings in the rest. Despite best efforts 5 patients succumbed to the sequelae of sepsis. Unsafe abortions and maternal mortality has a downward trend over the years, but still is a substantial burden on the economy. Regulations that force women to travel to attain legal care and face waiting periods lead to loss of income and other financial costs, and can make abortion inaccessible to women of low socio economic status. Therefore, availability of trained personnel and subsidized comprehensive abortion care services at the community health care centre level is the need of the hour.